Adoption of Integrated Crop Management (ICM) Level On Rice Paddy Farming Agricultural Business - Akiyana, Akiyana; Evahelda, Evahelda; Pranoto, Yudi Sapta (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol 14 No 2 (2020): Vol.14.No 2, 2020, 2020)
Poor level of knowledge and low level of technology adoption can reduce the production of a rice paddy in an agricultural business run by the farmer. Integrated Crop Management (ICM) is an innovation elaborated by the government to deal with these issues. Kepulauan Bangka Belitung Province through the Institute of Agricultural Assessment already implemented ICM to improve the production of crops. The study aims were to describe the Integrated Crop Management (ICM) and to analyze the factors that affected the ICM adoption in agricultural rice paddy business in Rias Village, Toboali District. This study was a survey study conducted in March until June 2019 involving 50 participants from farmer groups who implemented ICM, namely, Sinar Bone and Mekar Berkembang farmer group. Scoring method and multiple linear regression used to analyze the study result. There were three indicators used to describe the ICM level adoption: low, moderate, and high. Statistical analysis showed that the ICM components' adoption level was classified into a high category with a mean of 118.17 points or 78.78%. But on the other side, the component of integrated pest management (IPM) was still classified on the low category with a total of point of 80 or 53.33%. The tillage system component was obtained the highest score with a total of point of 140 or 93.33%. Factors affected the ICM adoption level were education level, agricultural business experience, agricultural extention and the wide of the agricultural area.